The Impact of Tourism on Changing Cultural Form (Case Study: Balinese Traditional Lumbung Architecture): English - Putu Agung Prianta; Anastasia Sulistyawati (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2024)
The rapid development of tourism has challenged the existence of traditional Balinese lumbung. Many lumbungs have been converted into commercial premises for the needs of the tourist market. This research aims to understand the influence of tourism on architectural changes in traditional Balinese lumbungs and to find out the implications of the transformation of traditional Balinese lumbung architecture due to the influence of tourism. The study uses a holistic and descriptive analytical approach, with a qualitative methodology involving literature analysis, observation and interviews. The research results show that tourism has changed the architecture of Balinese lumbungs from placement and form to materials and function. Lumbungs are now often adapted for tourist comfort, using modern materials, and functioning as tourism facilities such as villas and cafes. Sizes and ornaments are adjusted to international standards, as well as the use of modern lighting and ventilation. The transformation of traditional Balinese lumbung architecture has influenced cultural values and environmental sustainability. The conversion of lumbungs causes loss of historical value and reduces local cultural identity. Commercialization ignores cultural heritage and sustainability, increasing the burden on local resources and waste. Local socio-economic changes occurred as many shifted from agriculture to the service sector, increasing social inequality. However, tourism has strengthened awareness and funding for conservation, and the adaptation of modern facilities has increased the function and relevance of lumbung/jineng.